Islamic Educational Philosophy on Contemporary Islamic Discourse: A Case Study of PAI Students at STITNU Sakinah Dharmasraya - Rani Safitri; Pely Welgya; Mayasiti Solihah; Suci Adillah; Susi Puspita Sari (The Future of Education Journal, 2025)
This study aims to examine the understanding and responses of students in the Islamic Education (PAI) Program at STITNU Sakinah Dharmasraya toward contemporary Islamic discourse from the perspective of Islamic educational philosophy. In the context of the ever-changing era, contemporary Islamic discourse requires reinterpretation and rethinking of Islamic teachings to be more relevant and contextual. Islamic educational philosophy serves as an essential foundation in shaping students' mindset to respond to contemporary issues while adhering to the core values of Islam. This research employs a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation involving 15 PAI students who actively participated in contemporary Islamic discussions. The results indicate that most students have a good basic understanding of Islamic educational philosophy but still face challenges in translating these principles into responses to contemporary issues such as pluralism, radicalism, gender, and religious moderation. The study concludes that strengthening the integration of Islamic philosophical studies with social realities in the PAI curriculum is necessary so that students can become intelligent, critical, and moderate agents of change in addressing the challenges of the times.